Dynamic determinants of the upper torso angular velocity in golf swing - Takagi, T. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to clarify the dynamic components of the upper torso angular velocity about its longitudinal axis during golf swing. Six right-handed golfers hit a golf ball to the net. Three dimensional kinematic data of swing motions were collected using motion capture system. The dynamic components of the upper torso angular acceleration during swing were calculated as a function of I)jo int toque, 2) gravity, 3) gyro-moment, 4) motion-dependent force, and 5) ground reaction forces. The present study found that the torso joint toque most contributed to the upper torso angular acceleration about its longitudinal axis. On the other hand, the shoulder joint toque and the motion-dependent force of the left arm negatively contributed to the angular acceleration of the upper torso about its longitudinal axis.